'A Nine-Month Head-Start': The Maternal Bond and Surrogacy. Issue 1 (1st January 2017) - Dow, Katharine
ABSTRACT: This article analyses how interviewees drew on the 'natural' concept of the maternal bond to make nuanced and contingent claims about motherhood and the ethics of surrogacy. Based on ethnographic fieldwork in Scotland with people who do not have personal experience of surrogacy, it describes how they used this 'natural' concept to make claims about the ethics of surrogacy and compares these claims with their personal experiences of maternal bonding. Interviewees expected that because of the experience of pregnancy, mothers have a 'nine-month head-start' in bonding with their children. While this valorises it, it also reproduces normative expectations about the nature and ethic of motherhood.